Genetic moderation of the association between adolescent romantic involvement and depression: Contributions of serotonin transporter gene polymorphism, chronic stress, and family discord. (3rd June 2015) - Starr, Lisa R.; Hammen, Constance
Abstract: Studies support a link between adolescent romantic involvement and depression. Adolescent romantic relationships may increase depression risk by introducing chronic stress, and genetic vulnerability to stress reactivity/emotion dysregulation may moderate these associations. We tested genetic moderation of longitudinal associations between adolescent romantic involvement and later depressive symptoms by a polymorphism in the serotonin transporter linked polymorphic region gene ( 5-HTTLPR ) and examined contributory roles of chronic stress and family discord. Three hundred eighty-one youth participated at ages 15 and 20. The results indicated that 5-HTTLPR moderated the association between age 15 romantic involvement and age 20 depressive symptoms, with strongest effects for short homozygotes. Conditional process analysis revealed that chronic stress functioned as a moderated mediator of this association, fully accounting for the romantic involvement–depression link among short/short genotypes. Also, romantic involvement predicted later depressive symptoms most strongly among short-allele carriers with high family discord. The results have important implications for understanding the romantic involvement–depression link and the behavioral and emotional correlates of the 5-HTTLPR genotype.